1995
DOI: 10.1227/00006123-199504000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naloxone on Sodium- and Potassium-activated and Magnesium-dependent Adenosine-5′-Triphosphatase Activity and Lipid Peroxidation and Early Ultrastructural Findings after Experimental Spinal Cord Injury

Abstract: Endorphins have been implicated in the pathophysiology of spinal cord injury. The effect of naloxone on the sodium- and potassium-activated and magnesium-dependent adenosine-5'-triphosphatase (Na(+)-K+/Mg+2 ATPase, EC.3.6.1.3.) activity, lipid peroxidation, and early ultrastructural findings were studied in rats at the early stage of spinal cord injury, produced with an aneurysm clip on the T2-T7 segments. The rats were divided into four groups. The 10 rats in Group I, which had no injury and received no medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…32 Many researchers have shown that agents inhibiting lipid peroxidation enhance functional recovery in experimental CNS injuries. 13,14,33,34 This concept was supported clinically by NASCIS II. 35 The extent of lipid peroxidation is a useful parameter for evaluating the cellular disturbance caused by spinal cord trauma in experimental conditions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…32 Many researchers have shown that agents inhibiting lipid peroxidation enhance functional recovery in experimental CNS injuries. 13,14,33,34 This concept was supported clinically by NASCIS II. 35 The extent of lipid peroxidation is a useful parameter for evaluating the cellular disturbance caused by spinal cord trauma in experimental conditions.…”
Section: Discussionmentioning
confidence: 90%
“…35 The extent of lipid peroxidation is a useful parameter for evaluating the cellular disturbance caused by spinal cord trauma in experimental conditions. 13,14,33 There are several methods for measuring the degree of lipid peroxidation in tissue. These methods are measurement of thiobarbituric acid reactive substances (TBARS) content, determination Epidural cooling in SCI S Tu Èzgen et al of changes in diene conjugation aliquots of lipid extracts, and measurement of formation of lipid soluble¯uorescent material.…”
Section: Discussionmentioning
confidence: 99%
“…7,24,25 The pathological lesion in the spinal cord injury requires 1 ± 2 h to develop. 24,26 This lag time is necessary to allow a delayed injury process.…”
Section: Discussionmentioning
confidence: 99%
“…7,24,25 The pathological lesion in the spinal cord injury requires 1 ± 2 h to develop. 24,26 This lag time is necessary to allow a delayed injury process. Secondary injury processes include ischemia, release of excitotoxic neurotransmitters, free radical generation, lipid peroxidation, and in¯ux of calcium ions in to the neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation